2016
DOI: 10.1021/acs.jpcc.6b00075
|View full text |Cite
|
Sign up to set email alerts
|

Silver Nanoparticles: Synthesis and Its Nanocomposites for Heterojunction Polymer Solar Cells

Abstract: We have reported the green synthesis of silver nanoparticles (AgNPs) using the aqueous extract of Sapodilla (Manilkara zapota) fruit as nontoxic and eco-friendly reducing material. The synthesized AgNPs were characterized and used for preparing nanocomposites with GO and PEDOT:PSS. We have compared the performance of polymer cells based on poly­(3,4 ethylenedioxy-thiophene):poly­(styrenesulfonate) (PEDOT:PSS) with AgNPs incorporated in graphene oxide (GO). The constructed structure of the solar devices was ITO… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
10
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
5
3
1

Relationship

1
8

Authors

Journals

citations
Cited by 28 publications
(10 citation statements)
references
References 57 publications
0
10
0
Order By: Relevance
“…The XRD patterns of the synthesised AgNPs have been presented in Figure 5. Notable Bragg reflections were observed at 2h values of 38.10, 44.25, 64.55 and 77.20, indicating the (111), (200), (220) and (311) of the Face-Centered Cubic (FCC) AgNPs, respectively [44,45]. These results obviously showed that the AgNPs were composed of highly crystalline nanostructures.…”
Section: Xrd Analysismentioning
confidence: 93%
“…The XRD patterns of the synthesised AgNPs have been presented in Figure 5. Notable Bragg reflections were observed at 2h values of 38.10, 44.25, 64.55 and 77.20, indicating the (111), (200), (220) and (311) of the Face-Centered Cubic (FCC) AgNPs, respectively [44,45]. These results obviously showed that the AgNPs were composed of highly crystalline nanostructures.…”
Section: Xrd Analysismentioning
confidence: 93%
“…However, during the enlarged syntheses, reproducibility is critically important for the potential technological applications of GQDs. In continuation of our research work [27][28][29], in this work we have reported that the pyrolysis of citric acid was carried out which on further addition of sodium hydroxide for maintaining the pH produced GQDs. The effect of different pH on the formation of GQDs was studied in detail.…”
Section: Introductionmentioning
confidence: 92%
“…It has even been observed an increase of 116% in OPVs devices containing GO-AgNPs-PEDTO:PSS compared to those containing only GO-PEDOT:PSS as active layer [32].…”
Section: Applications For Energy Harvesting Devicesmentioning
confidence: 99%